Derrone Inhibits Platelet Aggregation, Granule Secretion, Thromboxane A2 Generation, and Clot Retraction: An In Vitro Study. (11th March 2021) - Shin, Jung-Hae; Irfan, Muhammad; Rhee, Man Hee; Kwon, Hyuk-Woo
Abstract : Cudrania tricuspidata ( C. tricuspidata ) is widespread throughout East Asia and in China and Korea, and it is widely used as a traditional remedy against eczema, mumps, and tuberculosis. With regard to the aforementioned medical efficacy, various studies are continuously being conducted, and it has been reported that C. tricuspidata extract has various actions against inflammation, diabetes, obesity, and tumors. Therefore, we evaluated antiplatelet effects using derrone in C. tricuspidata. We examined the effect of derrone on the phosphorylation of vasodilator-stimulated phosphoprotein (VASP) and inositol 1, 4, 5-triphosphate receptor I (IP3 RI), and on the dephosphorylation of cytosolic phospholipase A2 (cPLA2 ), mitogen-activated protein kinases p38 (p38 MAPK ), and Akt, which affects platelet function and thrombus formation. Various agonists-induced human platelets were inhibited by derrone without cytotoxicity, and it also decreased the intracellular calcium level through the signaling molecule phosphorylations. In addition, derrone inhibited glycoprotein IIb/IIIa ( α IIb/ β 3) affinity. Thus, in the present study, derrone suppressed human platelet aggregation and thrombin-induced clot formation.